Pengaruh Pelayanan Purna Jual terhadap Keputusan Pembelian Kendaraan Roda Tiga Merek Nozomi pada Main Dealer CV. Sinar Abadi Jambi - Muhammad Habiburrahman (Science of Management and Students Research Journal (SMS), 2019)
After-sale service CV. Sinar Abadi Jambi provided is a guarantee, provision of accesories, services, maintenance and repairs, facilities and equipment. After-sales service is given in the hope of being able to retain customers who are likely to be able to repurchase if they feel satisfied by the product and the services provided. In addition, after-sales service is also provided in order to attract new consumers to buy the products offered. Moreover, for products that do need their own care and knowledge to master it. When viewed from a company perspective, the company is required to be able to develop its products. Not only selling good products and quality but also must pay attention to the additional services that accompany these products. The hypothesis of this research alleged that after-sales service has an effect on consumer purchasing decisions on CV. Sinar Abadi Jambi. This study uses variable measurements using a Likert scale. CV. Sinar Abadi Jambi which is located at JL. A. Thalib Simpang IV Sipin, Telanaipura, Jambi City, is one of the business entities appointed by brand holders to distribute and market products. From the calculation of the Likert scale obtained after-sales service variable (X) with an average value of 293.1. The variable Purchase Decision (Y) with an average value of 273.78 can thus be concluded to be Important. From the analysis of the value of t count on the After Sales Service (X) variable is 8.268 with a significance level of 0.000. Because the value of t count 8.268> t table value is 1.984 and the significance level is 0.000 <probability of significance α = 0.05, then Ho is rejected and Ha is accepted. This means that the variable after sales service individually has a good effect on consumer purchasing decisions. Companies need to establish branch offices or representatives in areas that have potential consumers that aim to make it easier for consumers to get the products they need from the company and reduce distribution costs for consumers